Coal Sector Returns and Oil Prices: Developed and Emerging Countries - Hasan, Mohammad Z.; Ratti, Ronald A. (International Journal of Energy Economics and Policy, 2015)
This paper examines the effect of oil price on coal sector stock returns. A multifactor market model is used to estimate the expected excess returns to the coal sector. A 1% increase in oil price return has a statistically significant positive impact on coal sector returns of between 0.06% and 0.20%. A 1% increase in coal price raises the return of coal sector returns by between 0.22% and 0.30%. Increased volatility in oil price return significantly reduces coal sector return. Participants in energy markets may perceive oil price as being determined globally and as providing information on demand for energy overall. Understanding the variables that affect the behaviour of the stock prices in the coal is of importance to market participants and policy makers, and is helpful in developing efficient hedging policies to deal with changes in energy prices Keywords: coal sector return; oil price; coal price JEL Classifications: G15; O13; Q4